2016
DOI: 10.1159/000444220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mirtazapine Treatment on Serum Levels of Brain-Derived Neurotrophic Factor and Tumor Necrosis Factor-α in Patients of Major Depressive Disorder with Severe Depression

Abstract: Background: This study evaluated the clinical efficacy of mirtazapine and its effect on serum brain-derived neurotrophic factor (BDNF) and tumor necrosis factor-α (TNF-α) levels in patients of major-depressive disorder (MDD) with severe depression. Methods: Patients (aged 18-60) with MDD diagnosed by DSM-IV criteria, and Hamilton Rating Scale for Depression (HAM-D) score ≥25 were included (n = 30). Mirtazapine was given in the doses of 30 mg/day. All patients were followed up for 12 weeks for the evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 28 publications
0
33
1
Order By: Relevance
“…In consequence of MDD-related stress it influences the vagal afferent pathways associated with hypothalamus-pituitary-adrenal axis promoting inflammatory processes in CNS. Numerous studies showed TNF-α decrease post antidepressant treatment, although it is inconsistent with our results [Gupta et al, 2016;Halaris at al., 2015;Li et al, 2013].…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
See 4 more Smart Citations
“…In consequence of MDD-related stress it influences the vagal afferent pathways associated with hypothalamus-pituitary-adrenal axis promoting inflammatory processes in CNS. Numerous studies showed TNF-α decrease post antidepressant treatment, although it is inconsistent with our results [Gupta et al, 2016;Halaris at al., 2015;Li et al, 2013].…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
“…Some researchers proved that decreases of pro-inflammatory cytokines were more pronounced in patients who responded to treatment [Gupta et al, 2016;Li et al, 2013;Schmidt et al, 2016;Yoshimura et al, 2013]. The findings from those studies are supported by the Strawbridge et al meta-analysis which concluded that TNF-α, but not CRP, decreased in responders.…”
Section: Accepted Manuscriptmentioning
confidence: 89%
See 3 more Smart Citations